Wacana Perpanjangan Masa Jabatan Presiden (Analisis Wacana Kritis Norman Fairclough Pada Media Online Kompas.id Edisi Februari 2023) - Iqbal, Muhammad Yusuf; Mayasari, Mayasari; Tayo, Yanti (Peneliti.net, 2024)
Norman Fairclough’s Critical Discourse Analysis focuses on language as a tool of power practice. Fairclough’s CDA connencts text (micro) with the society context (macro) through the three basics analysis (Text, Discourse Practice, Sociocultural Practice) as the focus of the researcher in conducting an analysis of the discourse on extending the president’s term in February 2023 edition of Kompas.id. Qualitative descriptive is the method in this research. Researcher used literature studies and documentation technique. The research results show the linguistic tools used are diction, modality, intertextuality, interdiscursivity, and repetition. At the text production level is the Kompas Daily team which is distributed via online media kompas.id. At the text consumption level, there is no comment response because kompas.id is premium media from Kompas. On the macro dimension, the situational level is this news was motivated by the discourse on extending the term which re-emerged in 2023. At the institutional level, this news was influenced by MPR and legal experts from University of Indonesia. The social level of this news was the spread of the hashtags #2024Gantian and #TolakPerpanjanganMasaJabatan and demonstrations against extending the term by community groups and college students so that the MPR stated there was no suggestion regarding this discourse from MPR members.